2007
DOI: 10.1108/03074350710715854
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of performance of Malaysian Islamic unit trust funds

Abstract: Purpose -One of the implications of Islamic investment principles is the availability of Islamic financial instruments in the financial market. The main aim of this research is to observe the differences in terms of performance between Islamic and conventional mutual fund in the context of Malaysian capital market. Design/methodology/approach -To achieve the major objectives of this paper standard methods wereused for evaluating the mutual funds performance, for example, Sharpe index and adjusted Sharpe index,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

31
205
6
8

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(250 citation statements)
references
References 14 publications
(10 reference statements)
31
205
6
8
Order By: Relevance
“…Some studies have examined the performance of Islamic funds or socially responsible investing and compare that with conventional funds' performance. This includes (Mallin et al, 1995;Ludwig, 2005;Geczy et al, 2005;Elfakhani et al, 2005;Abdullah, 2007;Abderrezak, 2008;Hayat and Kraeussl, 2011;Mansor and Bhatti, 2009;Hoepner et al, 2009;Raphie andRoman, 2011, El Khamlichi et al, 2014). …”
Section: Literature Review On Islamic Indices Performancementioning
confidence: 99%
“…Some studies have examined the performance of Islamic funds or socially responsible investing and compare that with conventional funds' performance. This includes (Mallin et al, 1995;Ludwig, 2005;Geczy et al, 2005;Elfakhani et al, 2005;Abdullah, 2007;Abderrezak, 2008;Hayat and Kraeussl, 2011;Mansor and Bhatti, 2009;Hoepner et al, 2009;Raphie andRoman, 2011, El Khamlichi et al, 2014). …”
Section: Literature Review On Islamic Indices Performancementioning
confidence: 99%
“…They discovered that Islamic funds perform averagely similar to their conventional counterparts, and even are subject to multiple regimes (Hassan, Antoniou, and Paudyal, 2005;Elfakhani, Hassan, and Sidani, 2005;Hassan and Antoniou, 2006;Abdullah, Hassan, and Mohamad, 2007). Hoepner, Rammal, and Rezec (2011) also showed that Islamic funds from Malaysia or GCC neither significantly underperform their respective benchmarks nor are significantly affected by smallsize stocks.…”
Section: Islamic Portfolio Performancementioning
confidence: 99%
“…The longest investigation to date has been undertaken by Abdullah et al (2007) but they used method of Jensen alpha on 14 Malaysian Islamic funds over the period 1992-2001 and found these to significantly underperform the market benchmark.…”
Section: Prior Studiesmentioning
confidence: 99%
“…Empirical evidence on Islamic funds is scarce with extant studies analyzing the financial performance of less than 60 funds (Abderrezak, 2008;Abdullah et al 2007). The longest investigation to date has been undertaken by Abdullah et al (2007) but they used method of Jensen alpha on 14 Malaysian Islamic funds over the period 1992-2001 and found these to significantly underperform the market benchmark.…”
Section: Prior Studiesmentioning
confidence: 99%